Literacy in the science classroom - Tang, Kok-Sing; Tighe, S.; Moje, E. (2014)
Literacy is not a term often discussed among science educators. And yet, new standards in both science and English/Language Arts call for the teaching of literacy for scientific purposes within science classrooms. To many science teachers and students, however, the only time that literacy plays a role in science leaning is when students are asked to read-a request that is usually limited to a textbook passage-or when they are expected to write laboratory reports. In this chapter, we illustrate through four cases drawn from science classrooms how science literacy development is not only a central dimension of learning science, but also, of necessity, the purview of the secondary science teacher. Our stance is that science teachers are the most appropriate educators to teach the literacy practices of science because they are the people with expertise in the content and practices of science. We also illustrate how students can deeply learn both science content and science literacy when they are fully engaged with the literacy practices of science.